1994
DOI: 10.1073/pnas.91.13.6231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple genes in bovine retinal pericytes altered by exposure to elevated levels of glucose by using mRNA differential display.

Abstract: Cell Culture. Bovine retinal pericytes were obtained from fresh eyes as described (12) and cultured in Dulbecco's modified Eagle's medium (DMEM; 5.5 mM glucose) with 20% (vol/vol) fetal bovine serum. Prior to RNA isolation, the pericytes were grown to confluence and shifted into DMEM plus 1% (vol/vol) calf serum with glucose levels of either 5.5 mM, 22 mM, or 5.5 mM with 16.5 mM mannitol. Media were changed daily for 7 days, and the cells were stimulated with DMEM plus 10% fetal bovine serum for 8 hr (30 hr fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 57 publications
(33 reference statements)
3
42
0
Order By: Relevance
“…In the present study, eight possible candidate genes were suggested by the initial screening of -2,000 mRNA species and two of the eight showed reproducible differences in expression by Northern blot analysis, a rate of confirmed positives similar to that reported in previous studies (17,18). Genes previously identified as altered in the diabetic state such as GLUT-4 (34) and Ca2' ATPase (35) mRNA were not observed in this study, however, this may be due to several potential limitations of the differential display method such as the insensitivity of this method to quantitate small changes in gene expression as compared with Northern blot analysis and differences in primer efficiencies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the present study, eight possible candidate genes were suggested by the initial screening of -2,000 mRNA species and two of the eight showed reproducible differences in expression by Northern blot analysis, a rate of confirmed positives similar to that reported in previous studies (17,18). Genes previously identified as altered in the diabetic state such as GLUT-4 (34) and Ca2' ATPase (35) mRNA were not observed in this study, however, this may be due to several potential limitations of the differential display method such as the insensitivity of this method to quantitate small changes in gene expression as compared with Northern blot analysis and differences in primer efficiencies.…”
Section: Discussionsupporting
confidence: 64%
“…Total RNA was extracted using Ultraspec RNA isolation system (Biotecx Laboratories, Houston, TX). mRNA differential display was performed as previously reported (17,18 SDS, and 60 Mg/ml salmon sperm DNA at 65°C and washed in 0.5 x SSC, 5% SDS at 65°C for over 1 h. mRNA expression was quantified using a phosphorlmager and standardized volume integration with the accompanying ImageQuant Analyzing Software version 3.3 (Molecular Dynamics, Sunnyvale, CA) and loading differences were normalized using 36B4 as standard cDNA probe (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been reported, but not directly explained, also by others. 31,32 It is presumably related to the exponential nature of the PCR reaction and the probability that cDNA amplification may occasionally fail under the PCR conditions required for the differential display analysis.…”
Section: Differential Display Analysis Of Immunoselected Ma-11 Cell Pmentioning
confidence: 99%
“…After ultraviolet cross-linking, the membranes were prehybridized and hybridized to a 32 P-labeled bovine preproET-1 cDNA probe prepared by the multiprime DNA labeling system in 0.1 mol/l Pipes, 0.2 mol/l NaPO 4 , 0.1 mol/l NaCl, 1 mmol/l EDTA, 5% SDS, and 30 µg/ml salmon sperm DNA at 65°C. Stringent washing was done in 50% of 1ϫ sodium chloride and sodium citrate, 5% SDS at 65°C for over 1 h. The expression of mRNA was quantified with a PhosphorImager (Molecular Dynamics, Sunnyvale, CA) and normalized using 36B4 as the standard cDNA probe (34). In situ PKC activity assay.…”
Section: Methodsmentioning
confidence: 99%